A review of the intertidal Medon Stephens (Coleoptera, Staphylinidae, Paederinae) with description of a new species on the East Asian coasts - Kee-Jeong Ahn; Gae-Nam Jeon (ZooKeys)
A taxonomic review of the seashore-inhabiting Medon Stephens along the East Asian coasts is presented based on morphological and molecular characters (COI). Specimens of Medon calculosus Ahn & Jeon, sp. nov. and M. tomokoae Shibata & Fujimoto are extremely similar to each other, although there are differences in the form and structure of the aedeagus. Detailed comparison of morphological characters and molecular analyses based on genetic divergence and gene tree monophyly for species delimitation support the validity of the new species. Intraspecific genetic divergence of COI using uncorrected p-distance among Medon individuals ranged from 0% to 0.79%, while interspecific divergence among three Korean Medon species ranged from 7.74% to 11.69%. Morphological characters of M. calculosus Ahn & Jeon, sp. nov., M. prolixus (Sharp), and M. tomokoae are compared. The new species is described with illustrations of diagnostic characters and a key to species of the East Asian coastal Medon is presented.